Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kritis Siswa pada Pembelajaran Pendidikan Jasmani - Ari Mecky Prawira Ketaren; Edo Hamdani Oktavianus Sipayung (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
This study aimed to analyze the effect of the Problem-Based Learning (PBL) model on students' critical thinking skills in Physical Education learning at the fourth grade of SD Negeri 106790 Sei Mencirim. The study employed a quantitative approach using a pre-experimental method with a one-group pretest–Posttest Design. The participants consisted of 30 fourth-grade students selected using a total sampling technique. Data were collected through a critical thinking skills test, classroom observation sheets, and documentation. The research instruments were validated and tested for reliability prior to implementation. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, paired sample t-test, normalized gain (N-Gain), and Cohen’s effect size with IBM SPSS Statistics version 26. The findings revealed that the mean score of students' critical thinking skills increased from 55.50 in the pretest to 78.80 in the posttest. The paired sample t-test indicated a statistically significant difference between pretest and posttest scores (p < 0.05). The N-Gain result was classified as moderate, while the Effect Size indicated a very large educational impact. These findings demonstrate that the implementation of the Problem-Based Learning model effectively enhances students' critical thinking skills through problem-solving activities, collaborative discussions, investigation, and reflective learning processes. This study implies that Problem-Based Learning can serve as an effective instructional alternative to promote critical thinking skills and support student-centered learning in elementary school Physical Education.